2017
DOI: 10.1080/10410236.2017.1306910
|View full text |Cite
|
Sign up to set email alerts
|

From Menarche to Menopause: Understanding Multigenerational Reproductive Health Milestones

Abstract: Our study aims at understanding multigenerational communication among grandmothers, mothers, and daughters experiencing reproductive health transitions from menarche to menopause. Thirty women, 10 triads of grandmothers, mothers, and daughters, participated in narrative interviews to recount their menarche and menopause experiences. Analysis was read using a multilayered approach to interpret discourse positioned from self, reflexive others, and those stories informed by societal meanings. Four dialectical the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
3
1
1
Order By: Relevance
“…The above result is slightly different from the findings of other researchers who find that the average age at natural menopause as 51.4 years [17]. Whereas another study found that the age range was 45 to 55 years with the average age at 51 years [18].…”
Section: Discussion Of Findingscontrasting
confidence: 93%
“…The above result is slightly different from the findings of other researchers who find that the average age at natural menopause as 51.4 years [17]. Whereas another study found that the age range was 45 to 55 years with the average age at 51 years [18].…”
Section: Discussion Of Findingscontrasting
confidence: 93%
“…Menopause is more often viewed positively in cultures where ageing in general is valued [ 25 ]. Women’s interpretations of their symptoms depend on how ‘natural’ they are, or what their final period means to them [ 26, 27 ]. For some women, an end of physical fertility may be difficult, especially when fertility plays an important role in their identity as a woman.…”
Section: Menopause As a Life Phasementioning
confidence: 99%
“…However, cause and effect remain unclear. Menopause and midlife can be problematic for women, but they can also be a turning point, after which women experience more focus and room for careers and self-development [ 26 ]. Dennerstein et al showed that life events, daily activities, family life and job satisfaction all affect the mood of women during menopause [ 28 ].…”
Section: Menopause As a Life Phasementioning
confidence: 99%
“…La libertad va de la mano de una educación emocional que integre la realidad femenina, y esta debe tener referentes culturales que acompañen el proceso de empoderamiento desde la menarquía hasta la menopausia (Field-Springer et al, 2018). El placer va de la mano de la sexualidad, y esta, de los temas cercanos a la fertilidad y al conocimiento profundo del ciclo menstrual, que no ha de doler, no ha de producir asco, y mucho menos ser padecido en silencio.…”
Section: Cambio De Discursounclassified